The Paradox of Empathic Communication in Islamic Education (A Quantitative Analysis of Teacher–Student Interaction and Motivation in the Qur’an Memorization Program) - Husan, Ali; Yulianita, Neni; Zakiah, Kiki; Suriani Binti Othman, Siti (IJORER : International Journal of Recent Educational Research, 2026)
Objective: The relationship between empathetic communication by teachers and student learning motivation requires empirical verification in the context of traditional Islamic education, particularly in Qur'an memorization programs that emphasize an authoritative approach. This study addresses the knowledge gap regarding the motivational dynamics in Qur'an memorization learning, which has not been comprehensively documented. Methods: The study employed a cross-sectional survey design involving 83 students aged 15–18 years from four tahfidz institutions in the city and regency of Bandung through purposive sampling. Result: Empathetic communication was measured using the Dyadic Interpersonal Communication Scale (α = 0.916), while motivation was assessed using the Quranic Memorization Motivation Scale, which includes intrinsic (α = 0.843) and extrinsic (α = 0.811) dimensions. Hierarchical multiple regression analysis was conducted with demographic variables controlled according to Self-Determination Theory. The data indicate that empathetic communication predicts intrinsic motivation (β = -0.261, p = 0.015) and extrinsic motivation (β = -0.469, p < 0.001). The final regression models explained 35.8% of the variance in intrinsic motivation and 51.9% in extrinsic motivation; however, these R2 values reflect the combined contribution of empathetic communication and the controlled demographic variables (age, and memorization completion) with empathetic communication demonstrating a significant incremental effect beyond the controls. Novelty: These findings differ from Western educational theories, which predict a positive relationship, indicating that cultural context mediates the empathy-motivation relationship in traditional Islamic education. The study confirms the importance of adapting pedagogical approaches that consider local cultural values to optimize learning motivation in tahfidz programs.